Design and application of a puncture needle support (一种穿刺针支架的设计与应用) - WEI An (魏安); SUN Xiumei (孙秀梅); DU Chunliu (杜春柳) (中西医结合护理)
Puncture examination is a medical diagnostic technique in which a fine needle penetrates the skin and tissue to extract samples for laboratory analysis, so as to clarify the nature of the lesion, determine the pathogen, extract fluid or gas to relieve symptoms. Puncture needle support can effectively improve the efficiency and accuracy of puncture. This paper introduces the design and use method of a utility model puncture needle support, which can effectively improve the puncture effect, reduce the work burden of medical staff and improve the work efficiency. (穿刺检查是通过细针穿透皮肤和组织, 以抽取样本进行实验室分析, 用以明确病变性质、确定病原体、抽取积液或积气缓解症状的一种医学诊断技术。穿刺针支架辅助穿刺能够有效提高穿刺的效率和准确性。本研究介绍了一款实用新型穿刺针支架的设计和使用方法, 其有效提高了穿刺效果, 同时减轻了医护人员的工作负担, 提高了工作效率。)